1987
DOI: 10.1210/jcem-64-3-418
|View full text |Cite
|
Sign up to set email alerts
|

Early Effects of Cranial Irradiation on Hypothalamic-Pituitary Function*

Abstract: Hypothalamic-pituitary function was studied in 31 patients before and after cranial irradiation for nasopharyngeal carcinoma. The estimated radiotherapy (RT) doses to the hypothalamus and pituitary were 3979 +/- 78 (+/- SD) and 6167 +/- 122 centiGrays, respectively. All patients had normal pituitary function before RT. One year after RT, there was a significant decrease in the integrated serum GH response to insulin-induced hypoglycemia. In the male patients, basal serum FSH significantly increased, while basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 0 publications
1
34
1
2
Order By: Relevance
“…It does appear that ACTH deficiency is quite rare in patients receiving CRT at doses of <50 Gy [7], Previous reports of variable findings of abnormalities in cortisol reserve may be due to the use of different agents to test the HPA axis, as well as the fact that patients have been studied at varied times after treatment [15][16][17][18], Harrop et al [19] found adrenal reserve to be normal in 9 patients treated with high-dose RT for primary brain tumors, whereas Littley et al [20] reported that 3 of 7 adults tested 5-13 years after RT for brain tumors were ACTH-deficient. Lam et al [21] evaluated 31 patients after RT for nasopharyngeal carcinoma treated with doses in the range of 40-60 Gy and found a progressive decrease in basal cortisol levels. The mean integrated cortisol responses did not decrease significantly except in 1 pa tient who had a subnormal response 2 years after RT.…”
Section: Discussionmentioning
confidence: 99%
“…It does appear that ACTH deficiency is quite rare in patients receiving CRT at doses of <50 Gy [7], Previous reports of variable findings of abnormalities in cortisol reserve may be due to the use of different agents to test the HPA axis, as well as the fact that patients have been studied at varied times after treatment [15][16][17][18], Harrop et al [19] found adrenal reserve to be normal in 9 patients treated with high-dose RT for primary brain tumors, whereas Littley et al [20] reported that 3 of 7 adults tested 5-13 years after RT for brain tumors were ACTH-deficient. Lam et al [21] evaluated 31 patients after RT for nasopharyngeal carcinoma treated with doses in the range of 40-60 Gy and found a progressive decrease in basal cortisol levels. The mean integrated cortisol responses did not decrease significantly except in 1 pa tient who had a subnormal response 2 years after RT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to two prospective studies of patients given radiation doses of more than 3000 cGy, children (21,22) appeared to develop GH deficiency more rapidly than adults (23).…”
Section: Growth Hormone Deficiencymentioning
confidence: 99%
“…We included assessment of GH status, prolactin (PRL), and leptin expressed per kg body fat mass (Leptin/FM), because a close association of these neuroendocrine parameters with the sleep -wake rhythm has been demonstrated (11 -14). In addition, GH deficiency, hyperprolactinaemia and increased leptin concentrations have been reported in some patients treated with CRT (2,3,15,16). In order to gain insight into possible determinants of sleep changes, we performed stepwise regression analyses, with neuroendocrine status, radiation dose, chemotherapy, age at treatment and post-treatment interval as candidates.…”
Section: Introductionmentioning
confidence: 99%